ANALYSIS OF FACTORS CAUSING CHILDREN WITH SPECIAL NEEDS DROP OUT OF SCHOOL - Sari, Nova (STKIP An-Nur, 2019)
The results of the preliminary study found that there were still children with special needs who did not receive education yet. This showed that the education which is the right of every citizen including children with the special needs has not been fulfilled. This study aimed to determine the causes of children with special needs dropping out of school. Data were collected through interviews. The results showed that 2 children with special needs had never received fair education, 3 other children with special needs had obtained education but did not graduate from elementary school. The decision which did not continue education among them with special needs is due to the following factors: 1) Unequal education access for children with the special needs; 2) The parentsâ€™ economic situation on special needs children. 3) Misunderstanding the parents toward the potention and improvement on children with the special needs. 4) The parents shame on their children with the special needs.Â Keywords: Analysis of Factors; The Children With Special Needs; Dropout of School.